Upaya Peningkatan Asam Lemak Tidak Jenuh Susu Sapi Perah Dengan Suplementasi Lemak Terproteksi - , LILIS HARTATI, Prof Dr. Ir. Ali Agus, DAA., DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of the study were to obtain an effective method in protecting fat, to study the effect of the use of protected fat on rumen fermentation parameters, fatty acid profile of duodenal digested, blood plasma fatty acid profile, and to measure the effect of the protected fat usage on intake, nutrient digestibility, milk production, milk composition and fatty acid profile milk. The research was conducted in three phases. The first phase was the protection method of evaluation consisting of saponification methods and formaldehyde capsulation methods, then the protection result was tested in vitro by using palm oil as the source of fat and rejected skim milk as an ingredient for capsulator. The second phase, protected fat was tested by in vivo for the most effective protection methods using a single rumen fistulated and canulated duodenum dairy cow. The third phase, the in vivo test of protected fat was conducted towards 8 lactating dairy cows using a simple cross-over trial design. In the first stage, the dry matter digestibility, organic matter digestibility, free fatty acids, iodium numbers were observed, and for capsulation formaldehyde method was also tested by adding the protein digestibility and protein degradation rates. In the second phase, rumen pH, rumen ammonia, rumen VFA, duodenal digested fatty acid profile, and fatty acid profile of blood plasma were observed as well. In the third phase, digestibility of dry matter, organic matter digestibility, fatty acid profile of blood plasma, milk production, milk composition, and milk fatty acid profile was also observed. Results from this study are: the formaldehyde capsulation method gave significantly better results than the saponification method on dry matter digestibility, organic matter digestibility and free fatty acid level (P<0.01). Protected fat supplementation in livestock rations did not affect the pH, ammonia levels, rumen VFA, duodenal digested fatty acid profile, blood plasma fatty acid profile, dry matter digestibility and organic matter digestibility. Instead of affecting the composition of cow's milk (fat content, protein content, lactose content, dry matter content and BJ), the addition of protected fat in the ration, increased milk production and milk fat production (P<0.05). Fatty acid profile of milk was affected by the addition of protected fat on fatty acids capric, lauric fatty acid and oleic fatty acids (P<0.05). Keywords: Protected fat, Unsaturated fatty acid milk